2019
DOI: 10.3174/ajnr.a6237
|View full text |Cite
|
Sign up to set email alerts
|

Placement of a Stent within a Flow Diverter Improves Aneurysm Occlusion Rates

Abstract: BACKGROUND AND PURPOSE: Placement of a stent within a flow diverter has been described previously but its consequences have not been analyzed. We evaluated the clinical and angiographic results of stent placement within a flow diverter during the same treatment session. MATERIALS AND METHODS: All patients treated with a Surpass flow diverter were retrospectively evaluated. Patients with previously deployed stents and procedures in which scaffolding stents, a second flow diverter, or intrasaccular devices were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In series studies, complete occlusion was noted in 63% of aneurysms in early postmarket results, 8 82.6% of aneurysms in the study were not restricted to the circle of Willis, 46 and 93.9% of aneurysms had a stent placed within an FD. 47 The occlusion rate at the last follow-up treatment with an FD can even reach 100%. 48 In this pooled study, the complete occlusion rate of the FD group was 2.5-fold that of the CEV group.…”
Section: Discussionmentioning
confidence: 99%
“…In series studies, complete occlusion was noted in 63% of aneurysms in early postmarket results, 8 82.6% of aneurysms in the study were not restricted to the circle of Willis, 46 and 93.9% of aneurysms had a stent placed within an FD. 47 The occlusion rate at the last follow-up treatment with an FD can even reach 100%. 48 In this pooled study, the complete occlusion rate of the FD group was 2.5-fold that of the CEV group.…”
Section: Discussionmentioning
confidence: 99%
“…In Case 1, a braided stent was unable to be placed in the initial treatment because of marked kinking of the vessel at the neck of the aneurysm. We considered the possibility of recurrence at the time of initial treatment and planned to place an LVIS blue as a stent-in-stent by the scaffolding technique 16) in the event of recurrence. After retreatment using the LVIS blue, no recurrence was noted.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 9 ] There are few reports about combined usage of stents with flow diverters,[ 10 11 12 ] and recently, it has been shown that this technique reduces the time needed for complete aneurysm occlusion. [ 13 ] In this article, we describe a new technique, the exchange-free technique (EFT) that not only enhances the wall apposition of the surpass flow diverter (SFD) but also, in selected cases, allows us to anchor the landing zones by pinning the device by means of a laser-cut stent directly placed through the unique delivery system of the SFD. EFT provides a fast and easy way to appose and pin the Surpass device without a need to re-cross the deployed flow diverter.…”
Section: Introductionmentioning
confidence: 99%